Carlos Giménez, España, Una, Grande y Libre (1976-1977), and Comics of the Transition - Francie Cate-Arries (Dictatorships & Democracies, 2021)
I reexamine the Spanish Transition in terms of the interventions that cartoonists in the 1970s used to lay bare the machinations of the old regime still in power. Specifically, I analyze Carlos Giménez’s España, Una, Grande y Libre series, an exemplary counter-narrative against the dominant discourse produced by post-Franco government officials and economic power brokers. This collection—which denounces state-sanctioned violence and champions popular mobilizations in the name of a more just society—is also a pioneering work that makes visible the victims of the long-silenced crimes of Francoism.